Perioperative usage of eculizumab for prevention of recurrent thrombotic microangiopathy and graft dysfunction in a live related renal transplant recipient with atypical hemolytic uremic syndrome - Pavani S.; Stijitha S. B.; Lyander Livingston D.; K. Arun Chander Yadav; Venkatesh Rajkumar S. (International Journal of Basic & Clinical Pharmacology, 2026)
This case report describes about the graft protective role of perioperative eculizumab in a kidney transplant recipient with long standing atypical hemolytic uremic syndrome (aHUS), on 19 years of dialysis. A 30 years old male patient with history of systemic hypertension, chronic kidney disease, End stage renal disease, aHUS and Thrombotic micro‑ angiopathy on maintenance hemodialysis since 19 years was admitted for live related renal transplant. Eculizumab was administered perioperatively for prevention of complement mediated thrombotic microangiopathy (TMA) recurrence and graft loss. Following the surgery, the patient’s kidney function improved gradually, and his serum creatinine levels remained stable. There was no evidence of recurrent TMA. The patient was discharged with preserved graft function and advised regular follow up for monitoring of renal function and complement activity.